Senolytic Cocktail Dasatinib+Quercetin (D+Q) Does Not Enhance the Efficacy of Senescence-Inducing Chemotherapy in Liver Cancer - Kovacovicova, Kristina; Skolnaja, Marianna; Heinmaa, Mihkel; Mistrik, Martin; Pata, Pille; Pata, Illar; Bartek, Jiri; Vinciguerra, Manlio (Frontiers in Oncology, 2018)
Hepatocellular carcinoma (HCC) is a leading cause of cancer-related death, which develops in the context of fibrosis and cirrhosis caused by chronic inflammation, in turn due to non-alcoholic fatty liver disease (NAFLD), alcohol consumption and/or hepatitis viral infection. An increased number of senescent cells are associated with age-related tissue degeneration during NAFLD-induced HCC, or during chemotherapeutic treatment. Senolytic agents target selectively senescent cells. A combination of the senolytic drugs dasatinib and quercetin (D+Q) reduced hepatic lipid accumulation and alleviated age-associated physical dysfunction in mice. However, whether D+Q can impact the treatment of HCC, at the end-stage of the NAFLD inflammatory spectrum, is unknown. Here, using two well-established HCC cell lines (HepG2, Huh-7), we demonstrate that the maximal cytostatic doses for D and/or Q (1 + 1 μM) lacked efficacy in removing doxorubicin-induced β-gal-positive senescent cells. Moreover, D+Q did not affect doxorubicin-dependent induction of flattened morphology, activation of p16, expression of SASP-associated genes or formation of γH2AX foci. We then investigated the antitumor efficacy of doxorubicin, D+Q, or the combination, in xenograft studies conducted with HCC cells inoculated in athymic nude mice. Doxorubicin reduced tumor growth by 30% compared to control mice, while D+Q was ineffective in synergizing with doxorubicin and in clearing doxorubicin-induced HCC senescent cells. Unexpectedly, D+Q alone appeared to have acute pro-tumorigenic effects in control mice. While our data need to be confirmed in animal models that fully recapitulate NAFLD, we demonstrate that these compounds are ineffective, alone or in synergy with senescence-inducing chemotherapy, against experimental HCC.